2020
DOI: 10.1101/2020.05.25.114348
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Features Of Hippocampal Astrocytic Domains And Their Spatial Relation To Excitatory And Inhibitory Neurons

Abstract: The mounting evidence for the involvement of astrocytes in neuronal circuits function and behavior stands in stark contrast to the lack of detailed anatomical description of these cells and the neurons in their domains. To fill this void, we imaged >30,000 astrocytes in cleared hippocampi, and employed converging genetic, histological and computational tools to determine the elaborate structure, distribution and neuronal content of astrocytic domains. First, we characterized the spatial distribution of >19,000… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…To validate the spatial relationship between neurons and astrocytes, for each astrocyte the distance to the closest neuronal soma was calculated 13 ± 5 μm, ranging from 0.7 μm to 30 μm. The distribution falls within the range of literature observations, that is from 5 μm to 30 μm for three types of inhibitory neurons (Refaeli et al, 2020).…”
Section: Data Validation: Population-levelsupporting
confidence: 88%
“…To validate the spatial relationship between neurons and astrocytes, for each astrocyte the distance to the closest neuronal soma was calculated 13 ± 5 μm, ranging from 0.7 μm to 30 μm. The distribution falls within the range of literature observations, that is from 5 μm to 30 μm for three types of inhibitory neurons (Refaeli et al, 2020).…”
Section: Data Validation: Population-levelsupporting
confidence: 88%
“…CellDART could precisely localize the cells, especially for CA1, CA2, CA3, dentate principal cells, and entorhinal cortex, which are known to be restricted in specific anatomical locations (Supplementary Figure S13) (37). Also, astrocytes are found to have high density in stratum oriens and stratum radiatum and oligodendrocytes in corpus callosum as previously reported (38)(39)(40). In short, CellDART can be applied to spatial transcriptome with different spatial resolution.…”
Section: Application Of Celldart In Slide-seq Datasupporting
confidence: 72%
“…The performance of CellDART was tested by modulating the number of markers in each cell cluster from 5 to 80 (5,10,20,40,80) which corresponds to the total number of markers from 109 to 1157 (109, 203, 364, 642, 1157). It showed that setting total number of markers between 300 and 400 leads to overall high AUC value (Supplementary Figure S2A).…”
Section: Optimal Parameter Selectionmentioning
confidence: 99%
“…Complementary to the analysis of astrocytes' complex spatiotemporal activity will be the accurate quantification of their three‐dimensional structure (e.g., territory, arborization, microdomain structure) and intracellular organelle distribution (e.g., mitochondria, ER) with respect to their surrounding environment (e.g., excitatory and inhibitory synapses, neuromodulatory fibers, neuronal cell types). For example, astrocytes are in close contact with various types of neurons or neuronal structures and exhibit diverse morphologies across layers and tissue regions (Eilam et al, 2016; Lanjakornsiripan et al, 2018; Refaeli et al, 2021). The complex morphology and cellular environment place fundamental constraints on what kinds of signals astrocytes can sense, how they can be integrated locally and globally, and which types of commands they can transmit to neurons.…”
Section: Relating Astrocyte Functions To Neural Circuit Operation And...mentioning
confidence: 99%